Utilization of Digital Books in Increasing Students' Reading Interest: Pemanfaatan Buku Digital dalam Meningkatkan Minat Baca Siswa - Wirdiyana, Adhista Ayu; Sunaengsih, Cucun; Syahid, Aah Ahmad (Universitas Muhammadiyah Sidoarjo, 2024)
Along with the times, technology in its development certainly brings life changes, especially in the world of education which will also continue to develop. Nowadays all activities we can enjoy through mobile phones. The use of technology as a learning medium is an innovative step to improve the quality and quality of education in Indonesia, this can be seen in the Indonesian Ministry of Education which supports utilizing technology as a form of utilizing digital technology as a learning medium, namely by utilizing digital books. The purpose of this study is to provide new information about fun learning resources for students, namely through the use of digital books to increase reading interest. This study used the PTK method (classroom action research) using the research subjects of grade IV elementary school students at SDN Kebarepan 1 Kab. Cirebon totaling 30 students, using collections in the form of questionnaires, observations, interviews, and documentation. The results of the study in the form of an answered questionnaire disseminated by a researcher on the use of digital books showed that the use of digital books can increase students' reading interest as shown by an increase in their reading interest indicators, and can improve reading skills shown by an increase in their reading ability test results, starting from an average of 61 in the pre-PTK test, to 79 in the first cycle PTK test and to 83 in the second cycle PTK test.